The Power of Images and the Logics of Discovery in Psychiatric Care - Giovanni Stanghellini (Brain Sciences, 2022)
This paper, aligned with contemporary thinking in terms of patient-centered care and co-creation of patient care, highlights the limitations of the reductionist approaches to psychiatry, offering an alternative, “emergent” perspective and approach. Assuming that psychopathological phenomena are essentially relational, what kind of epistemological framework and ‘logic of discovery’ should be adopted? I review two standard methods I call ‘ticking boxes’ and ‘drafting arrows’. Within the ticking boxes framework, the clinician’s main goal is to discover whether a patient showing psychopathological phenomena meets pre-given diagnostic criteria. The process of discovery can be compared to two people assembling a puzzle where the patient has the pieces and the interviewer has the image of the completed design. Drafting arrows consists in constructing pathogenetic diagrams that display linear causative relationships between variables connected by an arrow to other nodes. These explanatory narratives include psychodynamic (motivational) and biological (causal) diagrams. I argue for a third approach called ‘linking dots’, a method of discovery based on the emergent properties of psychopathological phenomena. I build on and develop the approach to images and discovery devised by art historian Aby Warburg in his atlas of images Bilderatlas Mnemosyne. The visual constellations created by Warburg in the panels of the Bilderatlas can be understood as a method to reveal the layers of memory and the web of relationships manifested in them, inviting the viewer to participate in the production of meanings, forging ever new connections between the images. It is the viewer’s acts of perception that draw relationships between singularities. I suggest that this method is of enormous significance in the context of today’s socio-cultural transformation processes and related forms of psychopathological conditions, which can no longer be comprehended using the categories of existing knowledge systems.